Case Report: Kidney injury following non-medical massage - Truong, Michael Hieu; Tran, Vanessa Quynh; Tran, Spencer Doan; Nguyen, Calvin Tuan; Pham, Phuong Chi; Pham, Quynh Giao (Frontiers in Nephrology, 2026)
BackgroundDeep tissue massage is widely used for musculoskeletal pain and is generally considered safe. We report a case of acute kidney injury following non-medical deep tissue massage.Case presentationA 50-year-old healthy man presented with acute right lower quadrant abdominal pain 4 h after receiving a deep tissue massage for low back pain from an unlicensed therapist. CT angiography revealed a segmental acute infarction of the right kidney with occlusion of the superior segmental artery. The patient was successfully treated with anticoagulation therapy with gradual resolution of symptoms.ConclusionsThis case highlights the potential for severe vascular complications from deep tissue massage, even in healthy individuals. The proposed mechanism is direct mechanical trauma to the renal artery. Prompt evaluation of abdominal pain following massage is essential.